The practice of environmental education starting from the extension program Humaniza Bosque Carlos Belarmino (HBCB), Guarabira, Paraíba - Arruda , Luciene Vieira de; Belizário , Maria Aletheia Stedile; Borba , Geisa Karla de Oliveira; Araújo , Ana Paula de Oliveira; Araújo , Jaqueline Nascimento de; Costa, Jarbelly Karina da; Batista, Josilany Soares; Floriano, Edylma Thaís da Silva (Seven Editora, 2024)
Geographic Science has an assorted and diverse scope of analysis. One of the characteristics of geographic studies are the practices that can come forth from many contents studied in the classroom. Research and extension projects, in addition to enriching learning, favor the expansion of practices in relation to the environment in which students are included. The Humaniza Bosque Carlos Belarmino – HBCB extension project initially arises with the aim of managing and conserving an area within the Centro de Humanidades (CH) of the Universidade Estadual da Paraíba – UEPB. Currently, the project has become a program that houses more than 50 people, including teachers, students and volunteers, developing the topophilia of those who regularly visit these spaces. The program has 8 Environmental Education – EA projects taking its practices to more than 20 schools and communities, located in several municipalities polarized by the CH. The objective of this article is to present the practice of EA from the HBCB/CH/UEPB Extension Program. The methodology used was participatory and shared, with the scheduling of visits to interested schools and communities, as well as the activities developed within the HBCB space. The space has been well used and the proposed practices have had excellent acceptance from the university community and surrounding communities, who have become interested in applying EA practices in their municipalities, schools, streets and houses. In this way, it is understood that the extension work developed in the HBCB/CH/UEPB program contributes to strengthening education, developing sustainable environmental practices, strengthening the human/environment link, through topophilia. DOI:https://doi.org/10.56238/sevened2023.008-023